Análise da gestão de resíduos dos aparelhos pod system visando minimizar os impactos ambientais - Silva, Kelma Cristina Pereira da (Universidade Federal de São Carlos, 2023)
Pod systems are portable electronic devices used to vaporize liquids, usually e-juices containing nicotine or other flavors. They consist of a rechargeable or non rechargeable battery and a cartridge, which contains the liquid for vaporization. This academic work aims to demonstrate how much these devices harm human and environmental health, so a survey was carried out with the intention of gathering information on how these users should dispose of these "POD's", in the city of São Paulo, with a group of 190 people. The electronic cigarette appears as an attractive option for smokers of conventional cigarettes, believing that it can ease the addiction to smoking. Considered a novelty, electronic cigarettes have become a rage among young people and spread throughout the world. In Brazil, the sale is fully controlled by ANVISA due to the high level of toxic substances present in the device, which harms both human health and the environment. In addition, the controlled speed of this product, increasingly attractive also due to the variety of formats, colors and aromas, facilitates access to its consumption in coded scales. Furthermore, conventional cigarettes and electronic cigarettes share a similarity with each other: the presence of nicotine. In this way, it also adds a great environmental impact when considering the post-use residue. Due to the fact that it is a prohibited product, there are no proper guidelines for the disposal of e-cigarettes. This culminates in the disposal in any location, providing a high contamination of such chemical substances. It is relevant to visualize that the worrying effects caused to the environment, and also to human health, are a consequence of the use of electronic cigarettes only for recreational purposes, usually among young people.
Analysis of waste management of pod system devices aiming to minimize environmental impacts
Keywords: Cigarro eletrônico; Nicotina; Substâncias químicas; Impactos ambientais; Electronic cigarette; Nicotine; Chemical substances; Environmental impacts; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS